MENUJU PERTUMBUHAN INDUSTRI HIJAU DI SULAWESI SELATAN - Hatifa (Program Studi Administrasi Publik, 2024)
South Sulawesi Province, with the commitment and collaboration of the parties, needs to optimize further the transformation towards green industrial growth for the management of natural resources that ensure environmental sustainability and equal livelihoods for all levels of society. The Green Industry Index is a benchmark to evaluate the achievements and effectiveness of the transformation of Indonesian Industry towards a green Industry. The main principle of Green Industry is to create high industrial growth, along with encouraging social welfare and maintaining industrial quality and environmental carrying capacity. The Green Economy Index (GEI) or the Indonesian Green Industry Index consists of 15 indicators covering three pillars: Industrial, social and environmental. The policies that need to be in place implemented in the implementation of green industry in South Sulawesi are controlling land conversion through increasing the capacity of farmers by implementing climate change agriculture technology or climate-smart agriculture. Providing environmental services in the form of assistance or incentives for farmers who cultivate plants by maintaining the sustainability of the carrying capacity of their land or who contribute to improving environmental quality. Development of downstream natural resources using technology that does not harm the environment or surrounding communities and can provide high-added product value for farmers.